FINANCIAL BEHAVIOR: DETERMINASI MELALUI FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUDE PADA GENERASI MILLENIAL DI ERA SOCIETY 5.0 - Hartono, Pierdijono; Bormasa, Monica Feronica; Darmun, Darmun; Wartono, Tono; Ningrum, Endah Prawesti (JURNAL ILMIAH EDUNOMIKA, 2024)
The development of the global world has now entered the era of society 5.0, with advances in technology making financial management easier. The aim of this research is to determine the financial behavior carried out by the millennial generation in the era society 5.0 in terms of financial knowledge and financial attituted, which wiil help the millennial generation to be wiser in managing their finances. The method used in this research is a quantitative method with a descriptive approach. The results of this research, financial behavior can be seen from financial knowledge and financial attitude. In determining or determining attitudes in financial management, this can be done so that it will make it easier for students in the era of society 5.0 with advances in technology to organize and manage their finances. With this, it is necessary to increase students’ understanding of financial literacy. This aims to enable students to make decisions about technology-based financial management and wil make students’ lives easier in the era of society 5.0, which will enable students to manage finances effectively and afficiently in the era of society 5.0.